Some hydrozoans (Cnidaria) from King George Island, Antarctica - Galea, Horia R.; Schories, Dirk (Zenodo, 2012)
Galea, Horia R., Schories, Dirk (2012): Some hydrozoans (Cnidaria) from King George Island, Antarctica. Zootaxa 3321: 1-21, DOI:10.5281/zenodo.213236